Internal Marketing Analysis and Service Quality on Student Satisfaction as Consumers - Efdison, Zefri (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2021)
This study aims to analyze the effect of internal marketing and service quality on student satisfaction at the Sekolah Tinggi ilmu Ekonomi Sakti Alam Kerinci (STIE-SAK). The sample is 135 students. The sampling technique in this study was carried out by using non-probability sampling method. Data analysis using SPSS Version 25. Results the F test shows that the internal marketing and service quality variables simultaneously have a significant effect on student satisfaction. the effect of internal marketing and service quality on satisfaction is 48.8%.